2016
DOI: 10.1038/ctg.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hypocaloric High-Fiber and High-Protein Diet Improves Hepatic Steatosis Assessed by Controlled Attenuation Parameter

Abstract: OBJECTIVES:Non-alcoholic fatty liver disease is one of the most prevalent liver diseases and increases the risk of fibrosis and cirrhosis. Current standard treatment focuses on lifestyle interventions. The primary aim of this study was to assess the effects of a short-term low-calorie diet on hepatic steatosis, using the controlled attenuation parameter (CAP) as quantitative tool.METHODS:In this prospective observational study, 60 patients with hepatic steatosis were monitored during a hypocaloric high-fiber, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 49 publications
2
26
1
2
Order By: Relevance
“…Interestingly, we and others have shown that lifestyle interventions appear to be more effective in carriers of the PNPLA3 risk allele when compared to noncarriers, as evidenced in several studies. 34,35 We did not find differences in CAP values based on the TM6SF2 and MBOAT7 genotypes; however, a trend for higher CAP was observed based on the presence of risk alleles. This finding is in line with recent research supporting a stronger role of PNPLA3 as compared to TM6SF2 and MBOAT7 genotypes in terms of severity of hepatic-related injury.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, we and others have shown that lifestyle interventions appear to be more effective in carriers of the PNPLA3 risk allele when compared to noncarriers, as evidenced in several studies. 34,35 We did not find differences in CAP values based on the TM6SF2 and MBOAT7 genotypes; however, a trend for higher CAP was observed based on the presence of risk alleles. This finding is in line with recent research supporting a stronger role of PNPLA3 as compared to TM6SF2 and MBOAT7 genotypes in terms of severity of hepatic-related injury.…”
Section: Discussioncontrasting
confidence: 58%
“…32 Moreover, the PNPLA3 gene has been associated with increased risk of cardiovascular disease in the setting of type II diabetes. 34, 35 We did not find differences in CAP values based on the TM6SF2 and MBOAT7 genotypes; however, a trend for higher CAP was observed based on the presence of risk alleles. Interestingly, we and others have shown that lifestyle interventions appear to be more effective in carriers of the PNPLA3 risk allele when compared to noncarriers, as evidenced in several studies.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, a supplement of 5% guar gum in rat diets significantly reduced liver weight and lipid concentrations (Brockman, Chen, & Gallaher, ). It was this role of DF that has been shown to be beneficial for liver health (Arslanow et al., ; Reimer et al., ). This standpoint was also supported by our results, in which serum AST and ALT concentrations, indicators of liver health, were reduced by DF, thereby suggesting an improved liver health with increasing DF.…”
Section: Discussionmentioning
confidence: 99%
“…The FGF21 receptor then decreases serum FFAs by inhibiting visceral adipose from undergoing further lipolysis, inhibiting further hepatic TG synthesis, and promoting FFA oxidation and ketogenesis (90). Another smaller prospective study of 60 patients showed that a hypocaloric (1000 kcal/d) high-protein diet (41% protein, 29% carbohydrate, 24% fat, and 6% fiber) decreased liver stiffness, alkaline phosphatase, g-glutamyl transferase, lipid concentrations, and controlled attenuation parameters, or measurements of hepatic steatosis through transient elastography, by 14.0% (P < 0.001) (91). Thus, these studies are promising, but participants were only given a high-protein diet for short duration of time.…”
mentioning
confidence: 99%